Evaluate watchful waiting x emergency cerclage for isthmocervical incompetence (Research, Society and Development, 2023)
The study aims to evaluate watchful waiting in comparison with emergency cerclage for the treatment of isthmocervical incompetence. This is an integrative literature review carried out using the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE) databases. of the following Health Sciences Descriptors (DeCS): “expectant management” and “cervical cerclage”. Combined with each other by the Boolean AND operator. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme, in the last ten years (2012-2022). As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. 12 articles were found, after the combined search of descriptors and boleaning operators, 6 articles were selected to compose the final sample, as shown in the table below. The analysis of cervical incompetence is mainly based on the medical history and can be performed before or during pregnancy. Emergency cerclage is performed during the same period of dilation of the uterine cervix, and therapy for IIC should preferably be terminated by the 14th week of gestation, when cervical adjustments have not yet taken place and the time for early miscarriages has passed.